HUBUNGAN ANTARA FAKTOR PERSONIL PERENCANAAN PULANG DENGAN KELENGKAPAN RESUME MEDIS PASIEN DI RUMAH SAKIT UMUM DAERAH MABA KABUPATEN HALMAHERA TIMUR - Tahalele, Selfince; Mulyadi, Ns; Hamel, Rivelino (Universitas Sam Ratulangi, 2016)
Abstract. Medical summary can be a subject of study for quality control of medical records. Nursing activities are not optimal at this time is the patient's discharge planning activities. One of the factors that determine the success of the planning process was a factor of personnel discharge planning. The aim of research was to determine the relationship between the factors of personnel discharge planning with the completeness of patientâ€™s medical summary at the General Hospital of East Halmahera Regency Maba. Methods of analytic observational study using cross sectional design. This research was conducted at the General Hospital Maba of East Halmahera on February 29 to March 5, 2016. The samples were nurses and entry summary documentation with the quantities of each 34. The sampling technique was purposive sampling. Research instruments using questionnaires and observation guides. Data analysis was performed using chi-square test, at the significance level of 95% (Î± â‰¤ 0.05) indicates the value Ï = 0.012, this value is smaller than Î± = 0.05 and OR = 19,2. Conclusion: there is a relationship between the factors of discharge planning personnel with the completeness of patientâ€™s medical summary at the General Hospital Maba of East Halmahera Regency. Suggestions for nurses can improve performance especially in completeness of patientâ€™s medical summary to establish good communication between health professionals and patients and their families, although the number of nurses is still relatively small. Keywords :Personnel Discharge Planning Factor, Completeness Of Patientâ€™s Medical Summary Abstrak.Resume medis dapat menjadi bahan kajian untuk pengendalian mutu rekam medis. Kegiatan keperawatan yang belum optimal saat ini adalah kegiatan perencanaan pulang pasien. Salah satu faktor yang menentukan keberhasilan proses perencanaan pulang yaitu faktor personil perencanaan pulang. Tujuan penelitian untuk mengetahui hubungan antara faktor personil perencanaan pulang dengan kelengkapan resume medis pasien di Rumah Sakit Umum Daerah Maba Kabupaten Halmahera Timur.Metode penelitian observasional analitik dengan menggunakan desain cross sectional. Penelitian ini dilakukan di Rumah Sakit Umum Daerah Maba Kabupaten Halmahera Timur pada 29 Februari â€“ 5 Maret 2016.Sampel penelitian adalah perawat dan dokumentasi ringkasan masuk keluar dengan jumlah masing-masing 34.Teknik pengambilan sampel, yaitu purposive sampling.Instrumen penelitian menggunakan kuesioner dan panduan observasi. Analisis data dilakukan dengan menggunakan uji chi-square, pada tingkat kemaknaan 95% (Î± â‰¤ 0,05) menunjukkan nilai Ï=0,012, nilai ini lebih kecil dari Î±=0,05 dan OR=19,2. Kesimpulan : ada hubungan antara faktor personil perencanaan pulang dengan kelengkapan resume medis pasien di Rumah Sakit Umum Daerah Maba Kabupaten Halmahera Timur. Saran untuk perawat dapat meningkatkan kinerja mereka khususnya dalam kelengkapan resume medis pasien dengan menjalin komunikasi yang baik antara tenaga kesehatan maupun dengan pasien dan keluarga pasien walaupun jumlah tenaga perawat yang masih tergolong sedikit. Kata Kunci: Faktor Personil Perencanaan Pulang, Kelengkapan Resume Medis pasien.